Các hợp chất flavonoid và polyphenol từ cây mỏ quạ (Maclura cochinchinensis) - Chiến, Trần Văn; Như, Nguyễn Duy; Thủy, Ngô Thị; Công, Nguyễn Quốc; Anh, Nguyễn Thế; Thành, Nguyễn Tuấn; Thư, Nguyễn Minh; Thu Hà, Lê Thị; Thủy, Lê Thị; Bích Liên, Nguyễn Thị; Lộc, Trần Văn (Vietnam Journal of Chemistry, 2016)
From the ethyl acetate extract of Maclura cochinchinenis six flavonoids: kaempferol, dihydrokaempferol, quercetin, 6-p-hydroxybenzyl-dihydrokaempferol (gericudranin E), oxyresveratrol and 2',4',5,7-tetrahydroxy-flavanone (steppogenin) were isolated. Their structures were established by analysis of the NMR and mass spectra. Compound 6-p-hydroxybenzyl-dihydroquercetin was isolated for the first time from M. cochinchinenis.